Moving from Principles to Practice: Recommended Policy Changes to Promote Family-Centered Care - Kilmer, Ryan P. (2010)
This paper emphasizes the value of family-centered care. Discussion highlights family-centered philosophies (e.g., Systems of Care [SOCs]) and practice models (i.e., wraparound) and identifies discrepancies between conceptualizations and actual practice. Data from multiple sources detail issues in fidelity to family-centered values and needs and risks experienced by siblings of children with severe emotional disturbance and their caregivers. This discussion provides a springboard for policy recommendations to strengthen family support programming and enhance family-centered care, from modifying funding streams such that systems extend their reach beyond children with full-blown, diagnosable problems (those meeting standards of “medical necessity), to supporting prevention and early intervention initiatives that address families as targets for intervention. Recommendations include ensuring that communities with SOC funding address the needs of families; broadening Medic-aid rules and definitions; expanding the range of reimbursable activities and services; and increasing funding for evaluating family-centered care models and family support programming.